NEETs and youth guarantee registration: Examining the link to past undeclared work - Rocca, A.; Agahi, O.; Beilmann, M.; Natalia Edisherashvili, N.; Marta, Elena; Mazzochi, P.; Higgins, O.; Pizzolante, F.; Prieto-Flores, Ò.; Rodrigues, R. B.; Rosa, M.; Simões, F. (Politics and Governance, 2024)
A myriad of factors influence young people’s vulnerability and the likelihood of becoming NEET. Moreover, the share of young NEETs in European countries is very high. Institutional and governmental initiatives aiming to promote the inclusion of young people in the labour market are of paramount importance. However, the socio‐economic conditions and the level of vulnerability alongside other socio‐demographic characteristics are likely to influence the extent to which young people ultimately engage with such programmes. The current study ascertains whether previous experience of informal work increases young people’s propensity to participate in programmes offered by public employment services, such as the Youth Guarantee Programme. Indeed, we hypothesise that the experience of working without a contract makes young people more aware and concerned about the risk of remaining trapped in a spiral of vulnerable jobs. To test this, we used data from a survey of 4,273 NEETs and focused on Italy, Portugal, and Spain. The study’s findings contribute to a better understanding of the relationship between past experience in the informal economy and engagement with the Youth Guarantee. Besides contributing to the literature, the study can also contribute to policy making and practitioners’ assessment of the relative efficacy of Youth Guarantee initiatives among different subgroups of young NEET and tailor the interventions accordingly. In other words, the outcomes of this study should signal to governments that greater efforts should be made to implement initiatives reaching out to young people, as well as acting to reduce the precariousness in job contracts, which negatively impacts their quality of life.